2020
DOI: 10.26434/chemrxiv.11538708.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rational Enzyme Design Without Structural Knowledge: A Sequence-Based Approach for Efficient Generation of Glycosylation Catalysts

Abstract: <p>We present an enzyme engineering approach based solely on amino-acids sequence to convert glycoside hydrolases into transglycosylases. We demonstrate its effectiveness on enzymes form five different glycoside hydrolase families, synthesizing various oligosaccharides containing different α-/β-pyranosides or furanosides in one-step with high yields.</p>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Two subsite -1 residues contribute differently to the active site Mutations F26L and L352M display different effects on the T/H ratio of TxAbf, consistent with the fact that F26, a highly conserved residue in family GH51 [36], participates exclusively to subsite -1, whereas residue L352 (less conserved) [64] is located in a more ambiguous position between subsite -1 and the acceptor subsites. Both R69H-N216W-L352M and F26L-R69H-N216W demonstrate outstanding transglycosylation ability, coupled to low catalytic efficiency (kcat/KM).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 64%
See 2 more Smart Citations
“…Two subsite -1 residues contribute differently to the active site Mutations F26L and L352M display different effects on the T/H ratio of TxAbf, consistent with the fact that F26, a highly conserved residue in family GH51 [36], participates exclusively to subsite -1, whereas residue L352 (less conserved) [64] is located in a more ambiguous position between subsite -1 and the acceptor subsites. Both R69H-N216W-L352M and F26L-R69H-N216W demonstrate outstanding transglycosylation ability, coupled to low catalytic efficiency (kcat/KM).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 64%
“…Furthermore, an earlier study identified the mutation G179F that confers better xylotriose binding (Figure 2) [17]. Finally, in previous work F26L was pinpointed as a potential target to improve transglycosylation [43] and more recently this mutation was shown to confer increased ability to transfer the L-Araf glycone of the donor onto a xylotriose acceptor [36]. Significantly, F26 is also located in subsite -1, is 3.8 Å distant from E298 and lies in the vicinity (3.8 Å) of the O-5 position of the L-Araf moiety.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 89%
See 1 more Smart Citation
“…Further structural analysis shows that the acceptor locates above the donor glucose ring in a hydrophobic pocket constituted by Leu123, Phe124, Tyr149, Phe153, Ile188, and Leu202 (Figure S10), defining a cavity in which acceptors with an aromatic group can be easily accommodated. Out of 1356 sequences sharing 20−80% pairwise identity (average 42 ± 8.5%), 37 none of these hydrophobic residues is conserved, yet charged residues are not observed and polar residues amount for only 1% of observed residues at these positions, which relates to the documented promiscuity of GT1 enzymes with respect to hydrophobic acceptors. 7 Moreover, His26 is 99.4% conserved, while neither Glu nor Asp residues are observed.…”
mentioning
confidence: 98%